PERANCANGAN SISTEM INFORMASI ABSENSI PERSONIL DARAT DINAS PERHUBUNGAN KABUPATEN ASAHAN BERBASIS WEBSITE - Feby Wulandari Sembiring; Dewi Anggraeni; Ayu Anggraini (LPPM STMIK Royal Kisaran, 2023)
Abstract: In the era of rapid Information Technology advancement, speed, professionalism, and efficiency have become paramount demands in the workforce. Therefore, the crucial role of information technology in assisting and streamlining various tasks for humans in sectors such as schools, companies, universities, institutions, and government agencies is undeniable. This extends to the management of attendance in companies or government institutions. Attendance being a vital element in a government agency, where an efficient attendance system is expected to monitor and control employee performance to achieve maximum results in line with set objectives. However, there are still some companies or institutions that have not integrated their attendance system with information technology, as seen in the manual attendance process for ground personnel at the Asahan District Transportation Office in North Sumatra. To address this issue, this research aims to develop a web-based attendance system to facilitate administration and minimize the time required for attendance recording for ground personnel in the land transportation sector at the Asahan District Transportation Office. Keywords: Attendance; Department of Transportation; Information System Abstrak: Dalam era perkembangan pesat Teknologi Informasi, kecepatan, profesionalitas, dan efisiensi menjadi tuntutan utama dalam dunia kerja. Oleh karena itu, peran penting dari teknologi informasi dalam membantu dan mempermudah berbagai tugas manusia di berbagai sektor seperti sekolah, perusahaan, perguruan tinggi, lembaga, dan instansi pemerintahan tidak terbantahkan, termasuk dalam hal manajemen absensi di perusahaan atau instansi pemerintah. Absensi menjadi elemen vital dalam suatu instansi pemerintah, di mana dengan sistem absensi yang efisien, diharapkan dapat memantau dan mengendalikan kinerja karyawan dengan maksimal dan sesuai tujuan yang ditetapkan. Namun, masih terdapat beberapa perusahaan atau instansi yang belum mengintegrasikan sistem absensi dengan teknologi informasi, seperti halnya absensi personil lapangan darat Dinas Perhubungan Kabupaten Asahan yang masih menggunakan metode manual. Untuk mengatasi hal ini, penelitian ini bertujuan untuk mengembangkan sistem informasi absensi berbasis website guna memudahkan administrasi dan meminimalkan waktu pengisian absensi bagi personil lapangan bidang perhubungan darat di Dinas Perhubungan Kabupaten Asahan. Kata Kunci: Absensi; Dinas Perhubungan; Sistem Informasi